Entrepreneurial Orientation, Digital Self-Efficacy, and SME Business Performance Through Opportunity Recognition - Palupi Permata; Siti Sarah; Asti Nur Aryanti (Reviu Akuntansi, Manajemen, dan Bisnis, 2026)
Abstract Purpose: This study examines whether the interaction between entrepreneurial orientation and digital self-efficacy improves SME business performance through opportunity recognition within the internal business process perspective in culinary SMEs in West Java Province. Research Methodology: This study employed a quantitative approach with an explanatory survey method. Data were collected using questionnaires distributed to 301 culinary SME owners in West Java Province, Indonesia. The sampling technique was carried out through probability sampling using a cluster random sampling approach. Data analysis was conducted using Structural Equation Modelling (SEM) with SEM-AMOS Software. Results: The results indicate that entrepreneurial orientation and digital self-efficacy positively affect opportunity recognition, which in turn improves internal business process performance. Opportunity recognition partially mediates these effects, with digital self-efficacy, combining self-efficacy and digital literacy, playing a key role in enhancing SMEs’ ability to identify and develop opportunities. Conclusions: Strengthening entrepreneurial orientation and digital self-efficacy enhances opportunity recognition, which subsequently improves SME business performance from an internal business process perspective. Opportunity recognition serves as a critical mechanism linking entrepreneurial capability and digital confidence to performance. Limitations: This study is confined to culinary SMEs in West Java Province using a cross-sectional design, limiting generalizability to other sectors, regions, or longitudinal behavioral changes. Contributions: This study extends digital self-efficacy as an integrated psychological–digital construct and enriches SME performance literature through an internal business process perspective. Practically, it provides guidance for SMEs, policymakers, and development institutions to strengthen entrepreneurial orientation and digital self-efficacy via opportunity recognition to improve business performance.